The HST-Hyperion Survey: Grism Observations of a z ∼ 2.5 Protosupercluster - Ben Forrest; Lu Shen; Brian C. Lemaux; Ekta Shah; Olga Cucciati; Roy R. Gal; Finn Giddings; Emmet Golden-Marx; Weida Hu; Kaila Ronayne; Derek Sikorski; Priti Staab; et al. (The Astrophysical Journal)
We present the first results and catalogs from the HST-Hyperion survey. This survey has collected 50 orbits of WFC3/F160W imaging and WFC3/G141 grism spectroscopy in the most overdense regions of the Hyperion protosupercluster at z  ∼ 2.45, which are analyzed in conjunction with the adjacent 56 orbits of WFC3/F140W imaging and WFC3/G141 grism spectroscopy from the 3D-HST survey. Sources were identified and spectra were extracted using grizli , which subsequently fit the combined grism data with object-matched photometric data from the COSMOS2020 catalog to obtain a redshift and best-fit spectral model. Each source was then visually inspected by multiple team members and quality flags were assigned. A total of 12,814 objects with m _HST ≤ 25.0 were inspected, of which 5629 (44%) have reliable redshifts from the grism data and are sensitive to emission lines at a level of ∼8.8 × 10 ^−18 erg s ^−1 cm ^−2 (1 σ ). A comparison with high-quality, ground-based spectroscopic redshifts yields a scatter of σ _NMAD  = 0.0016. The resulting catalogs contain 125 confirmed members of the Hyperion structure within 2.40 <  z  < 2.53, with an additional 71 confirmed galaxies in projection within 2.35 <  z  < 2.65. The redshift, stellar population, and line flux catalogs, as well as all grism spectra, are publicly available.